Readmission and unplanned healthcare use after radical cystectomy are independent of discharge destination - Sandberg, Maxwell; Ye, Emily; Underwood, Gavin; Marie-Costa, Claudia; Roebuck, Emily; Catley, Sean; Seoane, Jorge; Deebel, Nicholas; Whitman, Wyatt; Wolff, Dylan; Xu, Mark; Namugosa, Mary; et al. (Canadian Urological Association Journal, 2025)
INTRODUCTION: Our primary purpose was studying utilization rates of home nursing assistance (HNA) and skilled nursing facility (SNF) placement after radical cystectomy (RC) and evaluating if their use was associated with emergency department (ED) visits, hospital readmissions, or mortality. Secondarily, we evaluated if patient socioeconomic status was associated with these factors following RC. METHODS: Patients who underwent RC for bladder cancer were retrospectively analyzed. Discharge destination was labeled as home, HNA, or SNF. The incidence of ED visits was recorded at 30 and 90 days after discharge from surgical admission. Readmissions were tracked similarly. Area deprivation index (ADI) was collected on each patient and organized in quartiles (ADIQ), with worsening socioeconomic status as ADIQ increased. RESULTS: A total of 215 patients were discharged home, 148 to HNA and 25 to SNF. ED visits and readmissions after RC at the 30- and 90-day marks did not differ based on discharge destination (p>0.05). Home patients had a lower incidence of death after RC compared to HNA and SNF (p=0.037), but not overall survival (OS) time (p=0.572). Readmission to the hospital after 30 days of discharge was more likely as ADIQ increased (p=0.017). Discharge destination, ED visits, and readmission after 90 days of discharge from RC were not different based on patient ADIQ (p>0.05). CONCLUSIONS: Discharge to home after RC is associated with lower mortality rates. Rates of readmission and use of ED resources appear independent of discharge destination. A greater ADIQ may interact with the likelihood of admission post-RC. Future efforts remain warranted to